2015
DOI: 10.1111/1467-8551.12145
|View full text |Cite
|
Sign up to set email alerts
|

To Divest or not to Divest: A Meta‐Analysis of the Antecedents of Corporate Divestitures

Kalin D. Kolev

Abstract: Corporate divestitures have been identified as important strategic actions with a positive impact on firm performance. Yet, what is still missing in the strategic management literature is an integrative framework that quantitatively synthesizes the relative impact of various antecedents to divestitures, and theoretically reconciles the multitude of theories underlying divestiture research. To fill this gap, the author conducts a meta-analysis (based on a sample of 35 studies) and develops four broad categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 105 publications
1
83
0
Order By: Relevance
“…To address the issue of endogeneity, the instrument variable (IV) approach is used (Baum, ). Marketing capabilities are suggested to be among the most important factors that directly influence FA performance (Morgan, Vorhies, & Mason, ), but they usually do not have a direct impact on an FA's exit (Kolev, ). Therefore, we chose two of the marketing capabilities, promotion capability and distribution capabilities, as our two IVs.…”
Section: Methodsmentioning
confidence: 99%
“…To address the issue of endogeneity, the instrument variable (IV) approach is used (Baum, ). Marketing capabilities are suggested to be among the most important factors that directly influence FA performance (Morgan, Vorhies, & Mason, ), but they usually do not have a direct impact on an FA's exit (Kolev, ). Therefore, we chose two of the marketing capabilities, promotion capability and distribution capabilities, as our two IVs.…”
Section: Methodsmentioning
confidence: 99%
“…We controlled for several factors linked to divesting firm financial performance (Bergh, 2017; Kolev, 2016; Lee and Madhavan, 2010). First, a considerable research stream reports that the stock market assessment of a divestiture is associated with the relatedness of the divested business to the primary business of the divesting firm (see Brauer, 2006; Lee and Madhavan, 2010, for reviews; e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the I 2 index describes the percentage of variability that is due to heterogeneity rather than to sampling error, the H 2 index is calculated as the ratio of the unaccounted-for variability in effect size to the level of sampling variability (Borenstein et al, 2009). Some authors even recommend using several different methods to triangulate heterogeneity analyses to detect the presence of moderating effects (Kepes et al, 2012(Kepes et al, , 2013 The difficulties to perform any of these heterogeneity analyses can be found for instance in the MA Kolev (2016) performed on the relationship between several variables and divestitures. He only tested heterogeneity by means of overlapping in confidence intervals to subgroups and he followed the H&S approach.…”
Section: Ma In Management: Main Differences With Clinical Researchmentioning
confidence: 99%